Improvement of Viability and Vigor of Lampung Local Upland Rice Seeds Using Magnetic Fields: an Effort to Strengthen Food Security - Dwijowati Asih Saputri; Aulia Novitasari (ORGANISMS: JOURNAL OF BIOSCIENCES, 2025)
The importance of food security as part of the Sustainable Development Goals (SDGs), with a focus on local upland rice varieties from Lampung that are drought tolerant but have limitations in seed viability and vigor after storage. The study aims to evaluate the effect of magnetic field exposure on the viability and vigor of upland rice seeds. The method used involves exposing the seeds to a magnetic field for durations of 3, 7, and 11 minutes, followed by measuring parameters such as germination percentage, mean germination time (MGT), coefficient of velocity of germination (CVG), and vigor index. The results showed that magnetic field exposure for 3 minutes produced the best results in several parameters, although not all differences were statistically significant. The magnetic field has the potential to improve the quality of upland rice seeds, but the optimal duration of magnetic field exposure cannot yet be determined